Wiedza jako nowy czynnik lokalizacji działalności gospodarczej w kontekście procesów integracji i globalizacji - Przygodzki, Zbigniew (Knowledge as a New Factor of Localization Economic Activity in the Context of Integration and Globalization, 2005)
The age of information with the rapidness, range and importance of changes that occur in social and economic life, is the revolution comparable to industrial revolution in the 18th century. The key issues for these changes are information flows with networks as the channels of communication. The main source of economic development is the people's ability to life-long learning and permanent improvement of qualifications. The knowledge with its environment and specific relations is the basic factor of localization of the economic activity.Knowledge is the resource while the information is the stream that flows out of it. The meaning of this elements has grown so high that today they are one of the key factors that decide about the allocation of economic resources. The primary source as well as the owner of knowledge, is the man. The man creates the knowledge in the process of interaction between the tacit and articulated knowledge, using the available information streams. Learning is both the individual and collective, or even more - social process. The knowledge creates itself the systems of diffusion. The systems that are able to self-organize.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 188-201